The seroprevalence of Anaplasma phagocytophilum in global human populations: A systematic review and meta‐analysis. Issue 5 (29th March 2020) - Wang, Feng; Yan, Min; Liu, Aihua; Chen, Taigui; Luo, Lisha; Li, Lianbao; Teng, Zhaowei; Li, Bingxue; Ji, Zhenhua; Jian, Miaomiao; Ding, Zhe; Wen, Shiyuan; et al.
Abstract: The tick‐borne pathogen Anaplasma phagocytophilum is an emerging infectious disease threat, but the overall A. phagocytophilum seroprevalence in humans is unclear. We performed a systematic search of English databases for literature published from 1994 to 2018. Studies reporting serological evidence of A. phagocytophilum infection in humans were included, and the information was extracted by two authors independently. As the study heterogeneity was significant, a random‐effects model was used to calculate the overall pooled seroprevalence. Data from 56 studies involving 28, 927 individuals from four continents were included. The seroprevalence reported by the studies ranged from 0% to 37.26%. The overall pooled A. phagocytophilum seroprevalence in humans was 8.4% (95% CI: 6.6%–10.4%). The seroprevalence was highest in high‐risk population (13.8%) and lowest in healthy population (5.0%). The estimated A. phagocytophilum seroprevalence of febrile patient, tick‐bitten and tick‐borne diseases populations was 6.4%, 8.0% and 9.0%, respectively. This meta‐analysis demonstrated first A. phagocytophilum seroprevalence estimates in different populations (healthy, febrile patient, high‐risk, tick‐bitten and tick‐borne diseases populations); it seems likely that present surveillance efforts are missing mild or asymptomatic infections of humans.